Discurso académico y libertad de cátedra: Las universidades católicas en el siglo XXI (Pontificia Universidad Católica Argentina, 2020)
Technology has changed not only the way that discourse happens, but also the discourse itself. Chair freedom is no longer measured by objective criteria, then, but by an enormous audience whose comparative criterion is disseminated collective representation and at the same time justified by digital networks. In this paper we are going to support two theses: First, (a) that technology has changed not only the way in which academic discourse occurs, but also academic discourse itself; and second, (b) that technology is an instrument for deconstruction of academic freedom, especially of academic freedom.